Amniotic Band Syndromewith Unique Clinical Presentations: A Case Report - Donel Suhaimi; Maya Savira; ShintaPuja Tilusari (Indian Journal of Forensic Medicine & Toxicology, 2021)
Amniotic band syndromeis a rare congenital disorder which associated with physical abnormalities suchas disruption, deformation, and malformations of organs. The most common abnormalities usually involvethe limbs that could range from simple constriction rings to complete amputation.In this case report, wereport anamniotic band syndrome with unique clinical presentations. The case was a new born male babywho was normally delivered and presented with a ring-like constriction at over middle right lower limband fusion (syndactyly) of left lower limb and right arm. In this report we also discuss different diagnosticmodalities which could be used in diagnosingamniotic band syndrome, the risk factors, type of amnioticband syndrome, post-natal diagnose, as well as the therapy.